The Prototype of Animal Intrusion Detection and Monitoring System using IoT - Alui, Noranisah; Masnani Mohamed (Evolution in Electrical and Electronic Engineering, 2023)
The encroachment of wild animals poses a major problem, resulting in the loss of valuable resources such as crops. This work presents a new approach that utilizes the Internet of Things (IoT) to detect and address the intruder in a specific area. For example, the invasion of wild animals in agriculture such as wild pigs and monkeys. This method combines the use of Passive Infrared (PIR) sensors, a camera, a buzzer, and the Blynk app. The PIR sensor works as an early warning system, detecting intrusion by wild animals. The buzzer is activated to deter and repel intruders. The camera is used for farm monitoring, while the Blynk app delivers real-time alerts to farm owners, ensuring immediate notification and intervention. By using this innovative model, farmers can effectively detect and prevent trespassing around the farm by activating the buzzer, thereby enhancing overall security and minimizing losses. It empowers farmer with a reliable and efficient system for early detection and intervention, allowing them to protect their crops, and property from potential threats posed by wild animals.